METODE RASULULLAH SAW MENDIDIK AHL ASH-SHUFFAH - Radiman Radiman (EL-TARBAWI, 2018)
This study aims to find out the method of the Prophet Muhammad educated Ahl al-Shuffah and the relevance of the method of the Prophet Muhammad to educate Ahl al-Shuffah with current Islamic education. The research method used is descriptive qualitative research design that aims to describe and to summarize various conditions, various situations, or various phenomena of social reality which exist in the community as the object of research. Analysis the data obtained in this study uses the Content Analysis strategy as a method of analyzing text and language. The results show that the method of the Prophet Muhammad in educating Ahl al-Shuffah included the method of giving advice, motivation methods, Intimidation methods, exemplary methods, discussion methods, persuasion methods, court methods, blessing methods, memorization, mulazamah, and game method. Then, this method shows the relevance that is closely related to the development of general education and Islamic education, especially at the present time Keywords: Ash-Shuffah, Islamic Education, Method